Technology Use and Job Performance of Academic Staff of Bishop Stuart University - Arinaitwe, Judith; Mwesigye, Adrian; Tibanyendera, Basil (East African Journal of Interdisciplinary Studies, 2024)
The study investigated the impact of technology use on job performance of academic staff. In particular, the study examined the influence of teaching technological use, managerial technological use, and research technological use on job performance of academic staff. Utilising a quantitative research approach, the study employed a correlational research design on a sample of 158 academic staff of Bishop Stuart University in Uganda. Data was collected using a self-administered questionnaire (SAQ). Data was analysed using descriptive statistics to show how the respondents rated academic staff technology use and job performance and Partial Least Squares Structural Equation Modelling to examine intricate relationships between variables and indicators. Descriptive results revealed that academic staff job performance was moderate while technology use was high. Structural equation analysis revealed that while managerial technology use had a significant and positive impact on academic job performance, research technology use and teaching technology use had a positive but insignificant influence on academic job performance. The study concluded that technology use for teaching and research has less contribution to job performance of academic staff but technology use for managerial purposes is vital for job performance of academic staff. The study recommended that university managers should employ more academic staff with PhDs such that besides teaching, they can effectively participate in research and community service activities, university managers should enhance academic staff use of technologies for research activities, and university managers should encourage academic staff to use technology for managerial purposes.
Keywords: Job Performance; Managerial; Research; Teaching; Technology Us